2018
DOI: 10.14785/lymphosign-2018-0013
|View full text |Cite
|
Sign up to set email alerts
|

Update on effects of cleaning agents on allergy and asthma

Abstract: Background: Cleaning and disinfecting agents are widely used in modern life, in homes, schools, public places, and workplaces as well as in recreational facilities such as swimming pools. Use has been for sanitizing purposes and to assist in reduction of infection as well as for deodorizing purposes. However, adverse respiratory effects have been associated with use of cleaning products ranging from effects in infancy and early childhood up to adults at home and work. Methods: This review summarizes recent pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…This difference from the conclusions of this HRA can be explained by differences in the selected toxicity values and the higher maximum exposures extrapolated from direct emission measurements (e.g., in the literature, no formaldehyde acute exposure exceeds 100 µg/m 3 (max: 82 µg/m 3 for a floor cleaner)). However, several reviews of the scientific literature, based on epidemiological studies mainly addressing professional uses, have shown an association between the use of cleaning products and various respiratory disorders, including an increased risk of asthma and of the intensity of associated symptoms [16,17,20,21,[58][59][60]. The strongest level of evidence relates to professional uses, but multiple studies have indicated situations of concern for household use [14,16,58,61].…”
Section: Chronic and Acute Risk Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference from the conclusions of this HRA can be explained by differences in the selected toxicity values and the higher maximum exposures extrapolated from direct emission measurements (e.g., in the literature, no formaldehyde acute exposure exceeds 100 µg/m 3 (max: 82 µg/m 3 for a floor cleaner)). However, several reviews of the scientific literature, based on epidemiological studies mainly addressing professional uses, have shown an association between the use of cleaning products and various respiratory disorders, including an increased risk of asthma and of the intensity of associated symptoms [16,17,20,21,[58][59][60]. The strongest level of evidence relates to professional uses, but multiple studies have indicated situations of concern for household use [14,16,58,61].…”
Section: Chronic and Acute Risk Characterizationmentioning
confidence: 99%
“…Cleaning products are widely used household consumer products [4,5] that are intended to make cleaning the house easier. They constitute a specific indoor emissions source of air pollutants, e.g., carbonyl compounds, aerosols, and terpenes [2,[6][7][8][9][10], and they are a subject of concern [11][12][13][14][15], especially for children [16,17] due to the specific metabolism and vulnerabilities associated with their developing bodies [18,19]. The associated risks should be better understood [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…9 A literature review on cleaning agents in health care settings emphasized that larger, more contemporary population-based studies of HCWs exposed to cleaning agents are needed. 34,[36][37][38][39] To assess the current prevalence of WRA among HCWs and whether changes in cleaning products exposure and tasks affected the prevalence, we conducted a population-based study of Texas HCWs and compared the findings to the 2003 study among the same target population.…”
mentioning
confidence: 99%
“…However, a recent report found no change in the percentage of WRA cases associated with cleaning agents, underscoring the need to increase the knowledge of potential cleaning hazards 9 . A literature review on cleaning agents in health care settings emphasized that larger, more contemporary population-based studies of HCWs exposed to cleaning agents are needed 34,36–39 …”
mentioning
confidence: 99%